Phenotypic convergence of bacterial adaption to sub-lethal antibiotic treatment - Wee, Gui Nam; Lyou, Eun Sun; Hong, Jin-Kyung; No, Jee Hyun; Kim, Soo Bin; Lee, Tae Kwon (Frontiers in Cellular and Infection Microbiology, 2022)
Microorganisms can adapt quickly to changes in their environment, leading to various phenotypes. The dynamic for phenotypic plasticity caused by environmental variations has not yet been fully investigated. In this study, we analyzed a time-series of phenotypic changes in Staphylococcus aureus during adaptation in response to antibiotic exposure using flow cytometry and Raman spectroscopy. The nine antibiotics, with four different modes of action, were used at sub-lethal concentrations to induce adaptation in the bacteria. Although the growth rate initially varied depending on the antibiotic used, most samples reached the maximum growth comparable to the control after 24 h. The phenotypic diversity, which showed remarkable changes depending on antibiotic treatment after 6 h, converged with the control after 24 h. In addition, cellular biomolecule content showed bacterial cells with enhanced tolerance to antibiotic stress with increases in cytochrome and lipid expression. Our findings demonstrated convergence into phenotypes with enhanced antibiotic tolerance in a short time when treated with sub-lethal concentrations and highlight the feasibility of phenotypic approaches in the advanced antibiotic treatment.